Multi-timescale and control-perceptive scheduling approach for flexible operation of power plant-carbon capture system. (1st January 2023) - Xi, Han; Zhu, Mingjuan; Lee, Kwang Y.; Wu, Xiao
Graphical abstract: Abstract: A carbon-capture system is required for coal-fired power plants to meet environmental regulation and provide support for grid penetration of renewable energy sources, when the integrated power plant-carbon capture system must operate in a highly flexible manner to accommodate the need for intermittent renewable power. To this end, this paper proposes a hierarchical scheduling scheme for the operation of integrated power plant-carbon capture system to fully exploit the decarbonization and flexibility of carbon capture technology in multiple timescales. The upper layer of the hierarchy implements a day-ahead stochastic scheduling to provide hourly operating instructions in the next 24 h so that the overall economic performance of the plant can be best achieved, including fuel consumption, load following and carbon trading. A novel index is then introduced to reflect the power adjustment contribution of carbon capture in the intraday scheduling layer and enhance the load ramping performance of power plant by flexible operation of the post-combustion carbon capture in minute timescale. In the lower layer of the hierarchy, control-perceptive scheduling based on close-loop dynamic model is proposed to coordinate the scheduling and underlying control, making the scheduling feasible for the operating practice. In addition, a new control system, which uses the reboiler steam flowrate to control the CO2 production rate and solvent circulation flowrate to control reboiler temperature is proposed to achieve superior flexibility support role of carbon capture. The case study shows that the proposed scheduling approach can improve the load tracking performance by 36.7% with satisfactory performance in carbon capture, which verifies the efficacy of the proposed scheduling approach in the power system. The impact of the proposed control system is also investigated, providing a broad insight on the flexible operation of carbon capture technology integrated with the power plant.